Octopus HRD: Multidiciplinary Approach to Higher Education Human Resources Development: Pengembangan Sumber Daya Manusia OCTOPUS: Pendekatan Multidisiplin untuk Pengembangan Sumber Daya Manusia di Perguruan Tinggi - Sari, Niki Puspita; Resmiatini, Erna; Muhammad, Helmi (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines human resource development techniques at Raden Rahmat Islamic University in Malang, Indonesia, using a multidisciplinary approach that integrates systems theory, economics, psychology, organizational development, anthropology, sociology, and communication. Employing a qualitative, exploratory descriptive design, data was collected through structured interviews, field observations, and supporting documentation analysis. Informants were selected through purposive and snowball sampling methods, and data was analyzed using an interactive approach, involving data collection, reduction, presentation, and conclusion drawing. Triangulation ensured research validity and reliability. The findings reveal that the university adopts a holistic human resource development strategy, combining various disciplines to enhance employee skills and performance. This approach not only helps the institution achieve its performance goals but also contributes to advancements in human resource development theory and practice